2009
DOI: 10.1007/s11665-008-9309-2
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Hot Corrosion of the Microstructurally Different Regions of 2.25Cr-1Mo (T22) Boiler Tube Steel Weldment

Abstract: This study examines the effect of microstructurally different regions on the hot corrosion of tungsten inert gas weldment in 2.25Cr-1Mo (T22) boiler tube steel. Various regions of weldment were oxidized in molten salt Na 2 SO 4 -60% V 2 O 5 environment at 900°C. The base metal was found to oxidize at much higher rates than the weld metal and the heat-affected zone. Oxide scales formed in the three regions were compared by scanning electron microscopy with energy dispersive of X-ray analysis, X-ray diffraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Thermo-gravimetric analysis (Figure 5) indicates that base metal shows the higher weight gain, and least was observed in the weldment. The results reveal that a high corrosion rate is found in base metal due to rapid Fe 2 O 3 scale formation, which is more porous and nonprotective, 6,9 and weldment shows the least corrosion rate. The PCGTA weldment shows better corrosion resistance.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Thermo-gravimetric analysis (Figure 5) indicates that base metal shows the higher weight gain, and least was observed in the weldment. The results reveal that a high corrosion rate is found in base metal due to rapid Fe 2 O 3 scale formation, which is more porous and nonprotective, 6,9 and weldment shows the least corrosion rate. The PCGTA weldment shows better corrosion resistance.…”
Section: Discussionmentioning
confidence: 97%
“…NaVO 3 acts as an oxygen carrier, which is diffused into the oxide scales through Fe 2 O 3 and further increasing the rate of oxidation. 9,14 The presence of NaVO 3 dissolves the Cr 2 O 3 protective oxide scale to form the Na 2 CrO 4, which is non-protective. The sulfur from the Na 2 SO 4 is diffused into the bare and weld metal through the cracks and starts to degrade it, which might be increasing the oxidation rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kumar et al, [31] Studied about hot corrosion of micro structurally different sections of 2.25Cr-1Mo (T-22) boiler tube welding. this study explains that even welded portions gets oxidized under molten salt Na2So4 -60% V 2 O 5 environment in boiler at 900%.the welding base metal is tungsten which gets easily oxidized under this environments at very higher rates can be studied by X ray techniques of various phase change and oxide formations.…”
Section: Studies On Thermal Spray Coatingmentioning
confidence: 99%
“…Kumar et al. 20 did research on the hot corrosion behavior of 2.25Cr-1Mo steel and its weldments using TIG welding and suggested that the weight gain of T22 base metal was much higher than the weight gain by the weld metal. The microstructural investigation of different weld region of T22 shows that base metal majorly comprises of ferrite (a white constituent) and pearlite.…”
Section: Introductionmentioning
confidence: 99%